HUBUNGAN DUKUNGAN KELUARGA DENGAN HARGA DIRI PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI DI RUANG DELIMA RSUP PROF. DR. R.D. KANDOU MANADO - Makisake, Juwita; Rompas, Sefty; Kundre, Rina (JURNAL KEPERAWATAN, 2018)
Abstrack : Introduction: Family support is a support that is beneficial to the individual gainedfrom his family and self-esteem is the result of an assessment of individual acceptance orrejection of himself. Purpose: This study aims to identify the relationship of family support tothe self-esteem of breast cancer patients undergoing chemotherapy in the Pomegranate RoomRSUP.Prof.Dr.R.D. Kandou Manado. Sample: This study was conducted to 52 breast cancerpatients who underwent chemotherapy. Research Design: This research is cross-sectionalresearch which is descriptive correlative, with slovin technique. Results Conclution: Theresearch instrument is a questionnaire that includes demographic data and statementsregarding family support and self-esteem. Data collection took place during March until April2018. The correlation test used in this research is Chi Square correlation test. The results ofthe study showed that family support had significant relation with self-esteem of breast cancerpatients who underwent chemotherapy in the Pomegranate Room of RSUP. Prof.Dr.R.D.Kandou Manado, the strength of good relationship and positive pattern (p = 0,000).Conclusion: It can be concluded that the higher the family support the higher the self-esteemof breast cancer patients undergoing chemotherapy in the Pomegranate Room of RSUP.Prof.Dr.R.D. Kandou Manado.Key Words : Family Support, Self-Esteem, Breast Cancer , ChemotherapyAbstrak : Pendahuluan: Dukungan keluarga adalah suatu dukungan yang bermanfaat bagiindividu yang diperoleh dari keluarganya dan harga diri merupakan hasil penilaian berupapenerimaan atau penolakan individu terhadap dirinya sendiri. Tujuan: Penelitian ini bertujuanuntuk mengidentifikasi hubungan dukungan keluarga dengan harga diri pasien kanker payudarayang menjalani kemoterapi di Ruang Delima RSUP.Prof.Dr.R.D. Kandou Manado. Jumlahsampel: Penelitian ini dilakukan kepada 52 pasien kanker payudara yang menjalani kemoterapi .Desain Penelitian: Penelitian ini adalah penelitian cross-sectional yang bersifat deskriptifkorelatif. Hasil Penelitian: Uji korelasi yang digunakan dalam penelitian ini adalah uji korelasiChi Square. Hasil penelitian menunjukan nilai (p=0,000) yang berarti Ha diterima atau adahubungan dukungan keluarga yang signifikan dengan harga diri pasien kanker payudara yangmenjalani kemoterapi di Ruang Delima RSUP. Prof.Dr.R.D. Kandou Manado, kekuatanhubungan baik dan berpola positif (p= 0,000 ). Simpulan: Dapat disimpulkan bahwa semakintinggi dukungan keluarga maka semakin tinggi harga diri pasien kanker payudara yangmenjalani kemoterapi di Ruang Delima RSUP. Prof.Dr.R.D. Kandou Manado.Kata kunci : Dukungan keluarga, harga diri, kanker Payudara, Kemoterapi